Kinetic Analysis of Food Systems - Marangoni, Alejandro G. (Springer International Publishing : Imprint: Springer, 2017)
This text provides a comprehensive and thorough overview of kinetic modelling in food systems, which will allow researchers to further their knowledge on the chemistry and practical use of modelling techniques. The main emphasis is on performing kinetic analyses and creating models, employing a hands-on approach focused on putting the content discussed to direct use. The book lays out the requisite basic information and data surrounding kinetic modelling, presents examples of applications to different problems and provides exercises that can be solved utilizing the data provided. Kinetic Analysis of Food Systems pursues a practical approach to kinetic analysis, providing helpful exercises involving chlorophyll degradation in processed vegetables, metabolic oscillations and sugar accumulation in cold-stored potatoes, transesterification of oils to manufacture biodiesel, aggregation of whey proteins to make protein gels and crystallization of fat stabilizers used in nut butters, among others. The book lays out the basics of kinetic modelling and develops several new models for the study of these complex systems. Taken together with the accompanying exercises, they offer a full portrait of kinetic analysis, from its basic scientific groundwork to its application.
Keywords: Chemistry.; Food -- Biotechnology.; Organic chemistry.; elektronické knihy; electronic books